BS56 Redox-regulation of AngII-induced cerebral microvascular damage in aging. (May 2019) - Geng, Li; Li, Jian-Mei
Abstract : Oxidative damage of cerebral vasculature has been found to play an important role in aging-related neurodegeneration. Endothelial oxidative stress attributable to the activation of a Nox2-containing NADPH oxidase is an early sign of age-related vascular abnormalities. However, the mechanism of aging-related Nox2 activation and cerebral microvasculature rarefaction remains unclear. In this study we used littermates of wild-type (WT) and Nox2 knockout (Nox2KO) mice at young (3–4 m) and old age (20–22 m) to investigate the role of Nox2-derived ROS in oxidative damage of cerebral microvasculature in aging. Compared to WT young mice, WT (but not the Nox2KO) aging mice had higher blood pressure and elevated serum levels of AngII. WT aging brains had significantly higher levels of AngII, increased ROS production, elevated lipid peroxidation, reduced capillary density and increased expressions of cell apoptosis markers i.e. increased p53 expression and γH2AX phosphorylation (p<0.05). However, these AngII-induced abnormalities were significantly reduced or absent in Nox2KO aging brains. The mechanism of AngII-induced Nox2 activation and cerebral endothelial oxidative damage was further investigated in vitro using primary cerebral microvascular endothelial cells isolated from mid-aged WT mice. AngII (100 μmol/L) increased significantly the levels of endothelial ROS production, Nox2 expression and p47phox phosphorylation. These were accompanied by increased ERK1/2 and γH2AX phosphorylation and p53 expression detected by Western Blot and damaged capillary formation on Matri-gels. However, all these AngII-induced oxidative responses were inhibited in the presence of a specific Nox2 inhibitor (Nox2-ds-tat). In conclusion, Nox2-derived ROS and redox signaling plays a critical role in regulation of AngII-induced cerebral microvascular rarefaction in aging. Conflict of interest: No